The prevalence and characteristics of phantom limb pain and non-painful phantom phenomena in a nationwide survey of 3,374 unilateral limb amputees - Diers, Martin; Krumm, Bertram; Fuchs, Xaver; Bekrater-Bodmann, Robin; Milde, Christopher; Trojan, Jörg; Foell, Jens; Becker, Susanne; Rümenapf, Gerhard; Flor, Herta (The journal of pain, 2022)
The experience of phantom limb pain (PLP) is a common consequence of limb amputation, resulting in severe impairments of the affected person. Previous studies have shown that several factors such as age at or site of amputation are associated with the emergence and maintenance of PLP. In this cross-sectional study we assessed the presence of several phantom phenomena including PLP and other amputation-related information in a sample of 3,374 unilateral upper and lower limb amputees. Clinical and demographic variables (age at amputation, level of amputation) explained 10.6% of the variance in PLP and perceptual variables (intensity of phantom limb sensation [PLS], referred sensations, intensity of telescoping, residual limb pain [RLP] intensity) explained 16.9% of the variance. These variables were specific for PLP and not for RLP. These results suggest that distinct variables are associated with PLP (age at amputation, level of amputation, PLS intensity, referred sensations, intensity of telescoping, RLP intensity) and RLP (PLP intensity) and point at partly different mechanisms for the emergence and maintenance of PLP and RLP. - Perspective - Clinical/demographic variables as well as perceptual variables are 2 major components related to PLP and explain ∼11% and ∼17% of the variance. These results could potentially help clinicians to understand which factors may contribute to chronic phantom limb pain.